Variations in cell signaling pathways for different vasoconstrictor agonists in renal circulation of the rat - Bauer, Johannes; Parekh, Niranjan (Kidney international, 2003)
Variations in cell signaling pathways for different vasoconstrictor agonists in renal circulation of the rat. - Background - Major cell signaling pathways involved in agonist-induced vasoconstriction are recognized to be Ca2+ mobilization via inositol-1,4,5 triphosphate (IP3), Ca2+ influx through l-type channels, activation of protein kinase C (PKC), and of Rho-associated kinase (ROK). However, their contribution for renal vasoconstriction induced by different agonists is not well characterized. - Methods - Increasing doses of angiotensin II (Ang II), norepinephrine, and arginine vasopressin (AVP) were infused into the left renal artery of anesthetized rats to reduce renal blood flow from a threshold value to about 50%. Rightward shift of the dose-response curves due to coinfusion of inhibitors served to assess contribution of different pathways: trimethoxybenzoate (TMB-8) against Ca2+ mobilization, nifedipine against Ca2+ influx, staurosporine and Ro-318220 against PKC, and Y-27632 and HA-1077 against ROK. Effects of inhibitors were also determined for renal response to a single dose of U-46619, a thromboxane A2 agonist. Composite response to U-46619 consisting of a fast and slow component did not permit determination of dose-response curves. - Results - Inhibition of ROK by Y-27632 or HA-1077 had the largest effect on renal responses to agonists. They shifted dose-response curves of Ang II, norepinephrine, and AVP to sevenfold and higher values. Staurosporine, nifedipine, and TMB-8 had variable effect on agonist responses. They attenuated effects of Ang II and norephinephrine in an additive manner, and each of them increased effective dose values about fourfold. TMB-8 did not attenuate response to AVP and U-46619. Staurosporine and nifedipine diminished effects of AVP in a nonadditive manner, and attenuated additively the fast component of U-46619 response. - Conclusion - In contrast to other cell signaling pathways, ROK plays a common role for all vasoconstrictor agonistsis in renal circulation.